On Sato–Tate distributions, extremal traces, and real multiplication in genus 2 - Kohel, David; Shieh, Yih-Dar (Arithmetic, Geometry, Cryptography and Coding Theory)
The vertical Sato–Tate conjectures gives expected trace distributions for for families of curves. We develop exact expression for the distribution associated to degree-